2016
DOI: 10.1093/ehjcvp/pvw007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiovascular risk of new drugs for the treatment of diabetes mellitus: risk assessment vs. risk aversion

Abstract: The Food and Drug Administration issued guidance for evaluating the cardiovascular risk of new diabetes mellitus drugs in 2008. Accumulating evidence from several completed trials conducted within this framework raises questions as to whether requiring safety outcome studies for all new diabetes mellitus therapies remains justified. Given the burden of cardiovascular disease in patients with diabetes, the focus should shift towards cardiovascular outcome studies designed to evaluate efficacy (i.e. to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…To date, no new sound adverse cardiovascular safety signal (including the risk for HF) has arisen from the trials with incretin‐based therapies (i.e. dipeptidyl peptidase 4 inhibitors and glucagon‐like peptide 1 receptor agonists), and there is now evidence of benefit from the EMPA‐REG trial with empagliflozin, a sodium–glucose co‐transporter 2 inhibitor …”
Section: Introductionmentioning
confidence: 99%
“…To date, no new sound adverse cardiovascular safety signal (including the risk for HF) has arisen from the trials with incretin‐based therapies (i.e. dipeptidyl peptidase 4 inhibitors and glucagon‐like peptide 1 receptor agonists), and there is now evidence of benefit from the EMPA‐REG trial with empagliflozin, a sodium–glucose co‐transporter 2 inhibitor …”
Section: Introductionmentioning
confidence: 99%
“…The CV safety of ADs is also important to determine [45], with the EMA recommending a long-term, controlled outcome study with 18-24 months of follow-up for ADs suspected to have an adverse CV effect [46]. A dedicated CV outcome trial was not necessary for insulin glargine/lixisenatide, as such studies conducted separately with each of its components (+ standard care) identified no safety concerns.…”
Section: What Is the Current Clinical Position Of Insulin Glargine/limentioning
confidence: 99%
“…Specifically, the upper bound of the 95% confidence limit of the hazard ratio for major adverse cardiac events (nonfatal myocardial infarction, non-fatal stroke, or cardiovascular death) should not exceed 1.30 at the end of the trial nor > 1.80 at any interim analysis (Guidance, 2008). The shortcoming of this guidance is that it ignored the important connections between T2DM and the risk of HF, progression of kidney disease, and other organ system illnesses (Zannad et al, 2016). Additionally, while it leveraged the endpoints that were associated with hyperglycemia (MI, stroke, cardiovascular death) it failed to provide a framework that could adapt to the mechanism of action of the drug or consider important unique safety events for adjudication (e.g.…”
Section: Cardiovascular Safety Assessed In Clinical Trials Of Antidiamentioning
confidence: 99%